Dieter Rams : the complete works - Klemp, Klaus, 1954- (Phaidon Press, 2020)
The ultimate reference on one of the most influential product designers of all time. For more than sixty years Dieter Rams has defined the look, feel, and function of some of the world's best-loved consumer items. Using his 'ten principles for good design' as a philosophy and practice for improving the industry in a more holistic, responsible way, Rams has built a reputation with global resonance. Here, for the first time, is a catalogue raisonne of every product that he has designed in his lifetime - a true celebration of his seminal contribution to the field of industrial and product design.
Keywords: Rams, Dieter, -- 1932-; průmysloví designéři -- Německo; průmyslový design -- 20. století -- Germany; industrial designers -- Germany; industrial design -- 20th century -- Germany; obrazové publikace; katalogy; pictorial works; catalogs